2023
DOI: 10.3390/met13091540
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Defect Characteristics on Prediction of Fatigue Life of TC4 Titanium Alloy Welded Joints

Yupeng Guo,
Furong Chen,
Mingkai Li
et al.

Abstract: The size and depth of defects significantly affect fatigue performance; the main purpose of this article is to clarify the effect of stress correction factors caused by defects on the fatigue life of α + β Type titanium alloy welded joints. In order to investigate the fatigue characteristics of α + β Type titanium alloy welded joints, axial constant amplitude loading fatigue tests were performed with a stress ratio of −1. The test results show that the fatigue life continues to increase as the stress amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[1][2][3][4] As one of the most common failures in engineering practice, fatigue is prone to occur under cyclic mechanical loading. It has been revealed that fatigue behavior of metal alloys is closely related to factors such as microstructural features, 5,6 and microdefects, 7,8 besides the macroscopic mechanical loading condition and environmental effects. Microstructures have a significant effect on the fatigue behavior of alloy materials, appreciably resulting in the dispersed fatigue life of crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] As one of the most common failures in engineering practice, fatigue is prone to occur under cyclic mechanical loading. It has been revealed that fatigue behavior of metal alloys is closely related to factors such as microstructural features, 5,6 and microdefects, 7,8 besides the macroscopic mechanical loading condition and environmental effects. Microstructures have a significant effect on the fatigue behavior of alloy materials, appreciably resulting in the dispersed fatigue life of crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the fatigue behaviors of Ti-6Al-4V joints, Balasubramanian et al [5] investigated the fatigue crack growth behavior of Ti-6Al-4V after GTAW, EBW, and LBW welding. Guo et al [6] studied TC4 using TIG welding and examined the impact of defect characteristics on fatigue life prediction. Liu et al [7] explored the crack closure characteristics of a novel titanium alloy.…”
Section: Introductionmentioning
confidence: 99%